State-community partnership as an option for sustainable management of an Androstachys johnsonii dominated woodland in Mabote District, Mozambique - Cuambe, Carla Cristina (Stellenbosch : Stellenbosch University, 2012)
Thesis (MscFor)--Stellenbosch University, 2004.